2021
DOI: 10.1108/jeee-09-2021-0354
|View full text |Cite
|
Sign up to set email alerts
|

University’s support for entrepreneurship and entrepreneurial intention: the mediating role of entrepreneurial climate

Abstract: Purpose Drawing on institutional theory, this paper seeks to untangle the relationship between university support for entrepreneurship and students’ entrepreneurial intentions. Specifically, this study aims to examine whether entrepreneurial climates within universities mediate the relationship between university support for entrepreneurship and students’ entrepreneurial intention. Design/methodology/approach Empirical data is drawn from 195 students across three Malaysian higher education institutions. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Based on the demographic profile, this study found that most respondents have obtained an undergraduate academic qualification (57.9%). Therefore, nurturing entrepreneurship should be started from home continuously up to the tertiary level (Sim et al , 2023). Characteristics of entrepreneurship and interest in entrepreneurship can be cultivated when the trainers use various teaching approaches that can attract the interest of an individual to venture into entrepreneurship (Hermann and Bossle, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the demographic profile, this study found that most respondents have obtained an undergraduate academic qualification (57.9%). Therefore, nurturing entrepreneurship should be started from home continuously up to the tertiary level (Sim et al , 2023). Characteristics of entrepreneurship and interest in entrepreneurship can be cultivated when the trainers use various teaching approaches that can attract the interest of an individual to venture into entrepreneurship (Hermann and Bossle, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The first step involves performing the confirmatory factor analysis (CFA), followed by the second step, where SEM is performed using SPSS and AMOS Graphics 25. Exploratory factor analysis (EFA) was not performed as the scales employed in this study were well-tested in prior studies, and no additions were made to the scale (Mahapatra & Mishra, 2017;Öğretmenoğlu et al, 2022;Sim et al, 2021). Additionally, Hair et al (2020) claimed that EFA is required when constructs have no prior patterns or hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identify factors that can influence the intention of a graduate to choose entrepreneurship as a career. Besides personality traits, an entrepreneur can be shaped by various factors that can be trained and learned (Sim et al, 2023). This includes social engagement in business, and encouragement from family members, peers (Ahmed et al, 2021), entrepreneurial values (Al-Lawati et al, 2022), education factor (Sim et al, 2023;Uddin et al, 2022), andcommunity andsurroundings (Al-Lawati et al, 2022) factors in motivating an individual to choose to become an entrepreneur.…”
Section: Factors Influences Entrepreneurship Interestmentioning
confidence: 99%
“…Another concern highlighted by Sim et al (2023) is that the engagement between academics and university students still needs to improve (Nungsari et al, 2023;Sim et al, 2023;Suffian et al, 2018). In empowering entrepreneurship as part of graduate employability, graduates often regard entrepreneurship as a second choice for the career pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation